Palladium–Cobalt Nanotube Arrays Supported on Carbon Fiber Cloth as High‐Performance Flexible Electrocatalysts for Ethanol Oxidation1. (4th February 2015) - Wang, An‐Liang; He, Xu‐Jun; Lu, Xue‐Feng; Xu, Han; Tong, Ye‐Xiang; Li, Gao‐Ren
Abstract: PdCo nanotube arrays (NTAs) supported on carbon fiber cloth (CFC) (PdCo NTAs/CFC) are presented as high‐performance flexible electrocatalysts for ethanol oxidation. The fabricated flexible PdCo NTAs/CFC exhibits significantly improved electrocatalytic activity and durability compared with Pd NTAs/CFC and commercial Pd/C catalysts. Most importantly, the PdCo NTAs/CFC shows excellent flexibility and the high electrocatalytic performance remains almost constant under the different distorted states, such as normal, bending, and twisting states. This work shows the first example of Pd‐based alloy NTAs supported on CFC as high‐performance flexible electrocatalysts for ethanol oxidation.